Assessing Information System Acquisition and Implementation Using COBIT 4.1 in Housing Developers - Dea Ramadhan; Hilyah Magdalena (Sinkron : jurnal dan penelitian teknik informatika, 2026)
Housing development companies plan, construct, and market housing. As technology advances, information systems become crucial, especially in financial matters. However, no comprehensive analysis of financial information system implementation in this sector exists. This study employed a qualitative descriptive approach supported by quantitative assessment (mixed-method), combining observations and semi-structured interviews (qualitative) with a questionnaire-based maturity level calculation (quantitative). Data were collected from three respondents (Finance Manager, IT Staff, and Accounting Staff) directly involved in the system. The maturity level was determined using the COBIT 4.1 framework in the Acquire and Implement (AI) domain. Results show an average maturity of 3.08 Level 3 (Defined Process), meaning procedures are documented and structured. However, several subdomains remain below target AI5 gap 1.30 and AI7 gap 1.10 require improved implementation and control of financial information systems, while AI3 has the smallest gap (0.02). This study contributes to the academic community by (1) providing a detailed assessment of financial information system implementation in housing development companies, (2) identifying maturity gaps in each AI subdomain, and (3) offering practical recommendations for improving IT governance maturity. Routine maintenance, system monitoring, and infrastructure updates are still needed to ensure system stability. Overall, information systems management has not yet reached the targeted maturity level due to reliance on individuals, lack of formal training, and poor procedure communication. Continuous improvement is required to make information systems management more efficient and scalable.